Biruta Rasiņa’s collection of scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) at the Latvian National Museum of Natural History, including type material of several species - Stalažs, Arturs (Zootaxa, 2021)
Information about the scale insect (Hemiptera: Coccomorpha) fauna of Latvia was first published in the second half of the 18th century, but the most serious and purposeful research on it was carried out between the 1920s and the early 1970s. Biruta Rasiņa, in collaboration with her colleagues, conducted the most extensive research on the scale insect fauna in Latvia in the 20th century. She was active in science from the 1940s until the early 1970s, and described eight new species between 1966 and 1971. According to modern taxonomy, seven names of the taxa she described are now synonyms of the names of other species, but one of her species names is still considered to be valid. Previously it was believed that the type material of the taxa she described, and all the other scale insect material she collected, had been lost. For an indefinite period of time the Latvian National Museum of Natural History had stored a collection of unaudited and still unregistered material, thought to be a collection of plant damages collected by Alfrēds Rasiņš. However, inspection of the material showed that it was in fact Biruta Rasiņa’s collection of scale insects, which contained both dry and ethanol-preserved material as well as microscope slides. The material has now been audited and registered in the museum’s collection. Most of the material was collected in Latvia, but the material also includes samples from other countries (Armenia, Belarus, Estonia, Georgia, Kazakhstan, Lithuania, Poland, Russian Federation and Ukraine). The collection includes samples of 75 species from eight families, of which 50 species were collected in the wild, 20 in greenhouses and indoors, and 5 species were found on imported fruits. Biruta Rasiņa’s collection of scale insects is the only known important collection of scale insects in Latvia, and is of national significance. A catalogue of the collection is therefore provided in this paper.